KUALITAS PELAYANAN DAN PENGARUHNYA TERHADAP TINGKAT KEPUASAN NASABAH DI BMT UGT SIDOGIRI CAPEM WARU - Rahmawati, Lilik; Hudayatin, Nofiana (El-Qist: Journal of Islamic Economics and Business (JIEB), 2014)
The quality of service has a close relationship with customer satisfaction. The quality of service provided an impetus to the customer to establish bonds of strong relationships with the company. When already interwoven bond, then the customer will choose the company and when they came to the company, they already have expectations about what kind of service will be obtained (acceptable) based on previous experience, communication, Word of mouth has ever heard, other information has ever been received, as well as the influence of the need. The service ever experienced will become the accepted standard of comparison services at this time. Based on that background, the outline of the problem surfaced, namely: whether quality of service indicators simultaneously influences on satisfaction clients in BMT UGT Sidogiri Waru Branch? Whether quality of service indicators affects customer satisfaction against partially in BMT UGT Sidogiri Waru Branch? And what indicators are most influential to the satisfaction of the customer in BMT UGT Sidogiri Waru Branch? The purpose of this research is to know the influence of partially and simultaneous, as well as the most dominant indicator of service quality on customer satisfaction levels in response to BMT UGT Sidogiri Waru Branch. The dimensions of service quality consist of intangibles, reliability, response, reassurance and empathy. This research uses descriptive quantitative methods, with incidental sampling technique with a number of respondents as much as 88 clients. The results of data analysis using regression analysis showed that, simultaneously, the quality of service which consists of intangible variables, reliability, response, reassurance and empathy to the customer with the highest level of satisfaction F_hitung > F_tabel 2,368 3,626 and significance of 0.005. Partially, intangible factors have a significant influence on the value significance of 0,249, whereas the factors of reliability, response, reassurance and empathy don’t have significant effects. The most dominant factor influence on satisfaction clients is a tangible factor, because the value of the significance of these factors most of 0.264. The regression equation is obtained as follows: Y = 5.492 + 0.179X1 + 0.115X2 + 0.122X3 – 0.007X4 + 0.113X5 indicates that increasing the quality of service in terms of intangibles can increase customer satisfaction.